1993
DOI: 10.3379/jmsjmag.17.s1_131
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Domain Nucleation and Growth in Magneto-Optical Recording Media

Abstract: Observations of micromagnetic dynamics in magneto-optical recording media have been performed using a static tester and a loop tracer. The magnetization reversal, domain structure and annealing treatment of amorphous rare earth-transition metal (RE-TM) alloy fIlms as well as multilayered cobalt-platinum (Co/Pt) thin films have been studied. The magnetization reversal was investigated in both nucleation-dominated and wall-motion-dominated media. The degree of jaggedness of various domain structures has been com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…When the applied magnetic field was swept to reverse the magnetization, we found that the coerclvity was higher within the hole region when compared \vith that outside the hole area [4,11] ; for instance, for the square holes domain wall motion coercivity outside the hole area for sampleDY273(Fe 8o C0 2o )n 7 is 2.7 kOe, while inside the hole area, the coercivity is 3.9 kOe. It seems that the magnitude of the coercivity of the hole arrays also depends on the hole geometry.…”
mentioning
confidence: 96%
“…When the applied magnetic field was swept to reverse the magnetization, we found that the coerclvity was higher within the hole region when compared \vith that outside the hole area [4,11] ; for instance, for the square holes domain wall motion coercivity outside the hole area for sampleDY273(Fe 8o C0 2o )n 7 is 2.7 kOe, while inside the hole area, the coercivity is 3.9 kOe. It seems that the magnitude of the coercivity of the hole arrays also depends on the hole geometry.…”
mentioning
confidence: 96%
“…A Digital Instruments Nanoscope IIIa SPM, equipped with phase extender [6] was used in this study. The magnetic tip with a CoCr-coated Si tip magnetized along the tip axis was used to scan the magnetic domain structures in the tapping-lift mode [7].…”
Section: B the Measurement Methodsmentioning
confidence: 99%
“…Observations have indicated that some of the media noise arises from domain irregularity, the jagged magnetization transition regions, and a nonuniform distribution of magnetization within recorded domains. [1][2][3] Consequently, a written domain with fixed shape and free from jaggedness could help reduce the media noise. One way to achieve this goal is by patterning of the disk substrates.…”
Section: ͓S0021-8979͑99͒38708-9͔mentioning
confidence: 99%